Soviet Paralels in the Politics of Bulgarian State against the Church in the First Years of the Communist Dictature - Karavaltschev, Ventsislav (Forum Theologicum Sardicense, 2025)
Ventsislav Karavaltschev, Soviet Paralels in the Politics of Bulgarian State against the Church in the First Years of the Communist Dictature. The article discusses the highlights of the activities of the Communist regime in Bulgaria after 9.ІХ.1944 in relation to the Church and their parallels in Russia after the revolution in 1917. Based on rich archival material from both the Bulgarian and Russian archives, the study clearly shows that any action of the Bulgarian Communist Party, concerning the Church was agreed in advance with Moscow. Even more, quite often the policy of Bulgarian Communist Party towards Bulgarian Orthodox Church was required and directed by the Russian communist and Moscow. The archives also show how deep the Communist system penetrated the Ecclesial body and how, from the very first days of the Communist coup in Bulgaria began to decompose from inside the Church.